Does Early Neonatal Thrombocytopenia Affect Ductal Therapeutic Response to Acetaminophen in Preterm Neonates? - Bin-Nun, Alona; Abu-Omar, Rawan; Shchors, Irina; Mimouni, Francis; Hammerman, Cathy (American Journal of Perinatology, 2022)
Objective Perinatal thrombocytopenia has been shown to affect responsiveness to therapeutic ductal closure with cyclooxygenase (COX) inhibitors. This has not been studied in responsiveness to acetaminophen, which has less effect on platelet function. The objective of this study was to evaluate whether thrombocytopenia affects ductal responsiveness to acetaminophen.Study Design This study was a retrospective review of preterm neonates <1,500 g. Echocardiograms were performed within the first week of life; if ductal status was found to be hemodynamically significant, infants were treated with acetaminophen.Results We studied 254 infants. Fifty-seven of these (22%) had a hemodynamically significant patent ductus arteriosus (hsPDA) and were treated with acetaminophen. Forty (70%) of those treated responded with ductal closure after one to two courses of acetaminophen. Seventeen infants were considered nonresponsive, requiring the addition of ibuprofen and/or surgical ligation. Sixty seven of the 254 infants (26%) developed moderate thrombocytopenia (platelets <100,000) within the first 10 days of life, more within the hsPDA group (54 vs. 18% p < 0.001); however, no differences in platelet-related parameters were observed between those who did and did not respond to acetaminophen treatment when comparing infants with hsPDA. Twenty-six of the 67 thrombocytopenic infants were already thrombocytopenic prior to acetaminophen treatment, and 19 of these 26 (73%) with pretreatment thrombocytopenia responded to acetaminophen treatment—with the overall response rate of 70%.Conclusions This study is the first to document that, in contrast to the COX inhibitors, there is no association between early neonatal thrombocytopenia and ductal therapeutic responsiveness to acetaminophen.Key Points
Keywords: acetaminophen; thrombocytopenia; patent ductus arteriosus; preterm neonate